A Novel Teaching Framework for Cultivating Moral Competencies in Guangzhou College Students - Liang, Yue; Chookhampaeng, Chowwalit; Jansaaeng, Apiradee (Journal of Posthumanism, 2025)
Moral education is crucial in shaping ethically responsible individuals, particularly in rapidly evolving societies such as Guangzhou. This research examines the effectiveness of a novel teaching framework designed to enhance moral judgment, moral emotion, and moral action among college students. Conducted at NanFang College Guangzhou, the research involved 35 students enrolled in the Morality and Rule of Law course during the autumn semester of 2024. A pre-test and post-test experimental design was implemented to evaluate the framework's impact. Three assessment tools were utilized: the Cultivate Moral Ability Questionnaire (a 22-item Likert scale), the Moral Education Test for College Students (a 40-question evaluation assessing ethical decision-making and moral reasoning), and the Moral Handwritten Report Project, which measured innovation, teamwork, and ethical analysis. Data were analyzed using statistical methods including Standard Deviation (SD), mean and t-tests, via IBM SPSS 30.0. The research uses statistical methods such as Descriptive Statistics, Paired Sample T-test, Wilcoxon Signed-Rank test and Chi-Square test. The results revealed a significant improvement in students' moral competencies following the implementation of the structured teaching framework. Post-test scores demonstrated enhanced ethical reasoning from 68.2 to 81.7 points, critical thinking from 66.1 to 80.2 points and teamwork skills from 64.7 to 77.9, with students exhibiting greater awareness of real-world moral dilemmas. The integration of experiential learning, case-based analysis, and interdisciplinary approaches proved effective in fostering moral development. This research highlights the importance of structured moral education frameworks in higher education. By incorporating interactive and interdisciplinary teaching methods, educators can more effectively cultivate ethical awareness and social responsibility among students. These findings provide valuable insights for the policymakers and educators aiming to enhance moral education in universities.